2020
DOI: 10.1063/5.0008341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topology upon relay synchronization in triplex neuronal networks

Abstract: Relay synchronization in complex networks is characterized by the synchronization of remote parts of the network due to their interaction via a relay. In multilayer networks, distant layers that are not connected directly can synchronize due to signal propagation via relay layers. In this work, we investigate relay synchronization of partial synchronization patterns like chimera states in three-layer networks of interacting FitzHugh-Nagumo oscillators. We demonstrate that the phenomenon of relay synchronizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the notion of relay synchronization has been extended from completely synchronized states to partial synchronization patterns in the individual layers of a three-layer multiplex network. It has been shown that the three-layer structure of the network allows for (partial) synchronization of chimera states in the outer layers via the relay layer [27][28][29][30][31]. Going towards more realistic models, time-delay plays an important role in the modeling of the dynamics of complex networks.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, relay synchronization has been illustrated in multi-layer and multiplex frameworks with different intra-layer topologies, such as Erdős-Rényi and scale-free [35]. In Reference [36], random inhomogeneities of the small-world type have been introduced in the network layers to scrutinize the robustness of relay synchronization. Continuous and discrete-time systems have been used as individual units to induce spatiotemporal structures in triplex networks [37,38].…”
Section: Introductionmentioning
confidence: 99%